.125D-3(D-7)=5.125D-3

Simple and best practice solution for .125D-3(D-7)=5.125D-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .125D-3(D-7)=5.125D-3 equation:


Simplifying
0.125D + -3(D + -7) = 5.125D + -3

Reorder the terms:
0.125D + -3(-7 + D) = 5.125D + -3
0.125D + (-7 * -3 + D * -3) = 5.125D + -3
0.125D + (21 + -3D) = 5.125D + -3

Reorder the terms:
21 + 0.125D + -3D = 5.125D + -3

Combine like terms: 0.125D + -3D = -2.875D
21 + -2.875D = 5.125D + -3

Reorder the terms:
21 + -2.875D = -3 + 5.125D

Solving
21 + -2.875D = -3 + 5.125D

Solving for variable 'D'.

Move all terms containing D to the left, all other terms to the right.

Add '-5.125D' to each side of the equation.
21 + -2.875D + -5.125D = -3 + 5.125D + -5.125D

Combine like terms: -2.875D + -5.125D = -8D
21 + -8D = -3 + 5.125D + -5.125D

Combine like terms: 5.125D + -5.125D = 0.000
21 + -8D = -3 + 0.000
21 + -8D = -3

Add '-21' to each side of the equation.
21 + -21 + -8D = -3 + -21

Combine like terms: 21 + -21 = 0
0 + -8D = -3 + -21
-8D = -3 + -21

Combine like terms: -3 + -21 = -24
-8D = -24

Divide each side by '-8'.
D = 3

Simplifying
D = 3

See similar equations:

| 21=-7*u+4(u+6) | | x^2-xy+3x^2+4xy= | | 2(v-7)+5*v=28 | | (x+1)(x-2)/x+3 | | 2(x+4)+3*x=-12 | | 7*y+23=4*y+8*y-22 | | x/5-12=4 | | -8=5x+3 | | k(2)-25=0 | | 2y+3=(y+21) | | 6*y+5=8*y+11 | | 28+19*x=-8+15*x | | 6x+8=11-4c | | -83=2*v-15*v-18 | | x+x+6x=119+6x | | 6x+8=-4x | | 3x=-2x-5 | | 5x+15/5=35-x | | 6x+8=11-4x | | 2x^3-5x=27 | | 4*x+43+2*x=7 | | (0.3+2x)(0.5+2x)=5.3018 | | -9*x-2*x-18=26 | | 108+(5x+8)=x | | -(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | x/2+x/4+x/5=x-1 | | w*5-7+w*2=-17 | | 3*3=8 | | 48-54+30= | | 63x^2-24x-15=0 | | -9(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | q^2+4q+4=26 |

Equations solver categories